2003
DOI: 10.1095/biolreprod.102.013532
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Subnormal Levels of Progesterone on the Pulsatile and Surge Mode Secretion of Luteinizing Hormone in Ovariectomized Goats1

Abstract: This study tested the hypothesis that endocrinological threshold levels of progesterone that induce negative feedback effects on the pulsatile and surge modes of LH secretion are different. Our approach was to examine the effects of subnormal progesterone concentrations on LH secretion. Long-term ovariectomized Shiba goats that had received implants of silastic capsules containing estradiol were divided into three groups. The high progesterone (high P) group received a subcutaneous implant of a silastic packet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
4
4
0
3
Order By: Relevance
“…The surge-like release of LH was similar to that observed in an ovulatory response in spontaneous estrous cycles of female Shiba goats (Mori and Kano, 1984). There is a general consensus that the endocrine condition of the luteal phase suppresses pulsatile and surge mode secretion of LH in mammals including goats (Kim et al, 2003). According to a previous study in sheep treated with CIDR for the synchronization of time of estrus (Van Cleeff et al, 1998), the interval between CIDR removal and the peak of spontaneous LH surge averaged 38.2 h (range, 24-52 h).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The surge-like release of LH was similar to that observed in an ovulatory response in spontaneous estrous cycles of female Shiba goats (Mori and Kano, 1984). There is a general consensus that the endocrine condition of the luteal phase suppresses pulsatile and surge mode secretion of LH in mammals including goats (Kim et al, 2003). According to a previous study in sheep treated with CIDR for the synchronization of time of estrus (Van Cleeff et al, 1998), the interval between CIDR removal and the peak of spontaneous LH surge averaged 38.2 h (range, 24-52 h).…”
Section: Discussionsupporting
confidence: 73%
“…The luteal phase elevation in circulating progesterone strongly inhibits GnRH secretion and, consequently, LH secretion, thereby preventing preovulatory LH surges (Goodman and Karsch, 1980;Skinner et al, 1998). It was experimentally demonstrated that progesterone blocks estradiol-induced LH surge in ewes (Blache et al, 1996) and goats (Kim et al, 2003). In the present study, the time-course of the LH response to TAK-683 treatment in the LC showed two phases.…”
Section: Discussionsupporting
confidence: 45%
“…The osmotic pump was subcutaneously implanted under brief anesthesia using ketamine chloride, and the flow rate for the administration was 10 μl/h. Five days after the start of TAK-683 or vehicle treatment, estradiol (Sigma Chemical, St. Louis, MO, USA) dissolved in 0.3% ethanol saline (0.6 μg/ml) was infused with a peristaltic mini pump into the jugular vein for 16 h at a rate of 6 μg/h through one of the catheters (18 gauge, Medicut; Nippon Sherwood Medical Industries, Tokyo, Japan) fitted bilaterally into the jugular vein in both groups, as described previously to evaluate the effects on the LH surge [25]. …”
Section: Methodsmentioning
confidence: 99%
“…The nadir and peak clusters for LH pulse detection were 2/2 points, and the t statistics for significant increase and decrease were 2/2. The LH surge was defined as the point when a sustained rise (for at least two consecutive points of blood sampling) in the plasma LH concentration exceeded twice the average baseline level during the pretreatment period before the estradiol infusion, as described previously [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Hasil ini tidak jauh berbeda dengan hasil penelitian Kim et al (2003) bahwa konsentrasi hormon estrogen pada saat estrus sekitar 105,5 pg/mL.…”
Section: Konsentrasi Hormon Estrogen Kambing Bligonunclassified